Diagnostic performance of the STOP-Bang questionnaire as a screening tool for obstructive sleep apnea in different ethnic groups - Waseem, Rida (J Clin Sleep Med, 2021)
STUDY OBJECTIVES: The STOP-Bang questionnaire is a concise and easy screening tool for obstructive sleep apnea (OSA). Using modified body mass index (BMI), we assessed the diagnostic performance of the STOP-Bang questionnaire in predicting OSA in ethnically different groups of patients undergoing surgery. METHODS: This was a multicenter prospective cohort study involving patients with cardiovascular risk factors who were undergoing major noncardiac surgery. Patients underwent home sleep apnea testing. All patients completed the STOP-Bang questionnaire. The predictive parameters of STOP-Bang scores were calculated against the apnea-hypopnea index. RESULTS: From 4 ethnic groups 1,205 patients (666 Chinese, 161 Indian, 195 Malay, and 183 Caucasian) were included in the study. The mean BMI ranged from 25 ± 4 to 30 ± 6 kg/m(2) and mean age ranged from 64 ± 8 to 71 ± 10 years. For the Chinese and Indian patients, diagnostic parameters are presented using BMI threshold of 27.5 kg/m(2) with the area under curve to predict moderate-to-severe OSA being 0.709 (0.665–0.753) and 0.722 (0.635–0.808), respectively. For the Malay and Caucasian, diagnostic parameters are presented using BMI threshold of 35 kg/m(2) with the area under curve for predicting moderate-to-severe OSA being 0.645 (0.572–0.720) and 0.657 (0.578–0.736), respectively. Balancing the sensitivity and specificity, the optimal STOP-Bang thresholds for the Chinese, Indian, Malay, and Caucasian groups were determined to be 4 or greater. CONCLUSIONS: For predicting moderate-to-severe OSA, we recommend BMI threshold of 27.5 kg/m(2) for Chinese and Indian patients and 35 kg/m(2) for Malay and Caucasian patients. The optimal STOP-Bang threshold for the Chinese, Indian, Malay and Caucasian groups is 4 or greater. CLINICAL TRIAL REGISTRATION: Registry: ClinicalTrials.gov; Name: Postoperative Vascular Events in Unrecognized Obstructive Sleep Apnea; URL: https://clinicaltrials.gov/ct2/show/study/NCT01494181; Identifier: NCT01494181. CITATION: Waseem R, Chan MTV, Wang CY, et al. Diagnostic performance of the STOP-Bang questionnaire as a screening tool for obstructive sleep apnea in different ethnic groups. J Clin Sleep Med. 2021;17(3):521–532.